Diffusive likelihood for interactive image segmentation. (July 2018) - Wang, Tao; Ji, Zexuan; Sun, Quansen; Chen, Qiang; Ge, Qi; Yang, Jian
Highlights: Diffusive likelihood strategy is proposed to obtain accurate estimation of prior probability from limited seeds. Superpixel-based grouping cues are introduced to enforce continuity for the object extraction. We construct the segmentation model by combining the geometrical adjacency and long range grouping cues. A joint optimization technique is utilized to solve a pair of sub-module functions Abstract: The performance of conventional interactive image segmentation methods is strongly affected by seed quantity and position, and it is difficult for them to maintain global data coherence due to the bias that is caused by limited interactions. Furthermore, the pixel-level relationships in these methods are too local to capture long-range connectivity cues, which often causes them to obtain under-segmented results. To solve these problems, this paper proposes an interactive segmentation method that is based on likelihood diffusion and perceptual learning. The diffusive likelihood strategy is proposed for accurately estimating the prior label probability from limited user inputs. Superpixel-level grouping cues are utilized to enforce continuity during the segmentation process. The geometrical adjacency and long-range grouping cues are fused in the proposed framework to ensure that the segmentation results maintain proximity and continuity. The final results can be obtained by applying a joint optimization technique to solve a pair of sub-module functions. Experiments on the Berkeley segmentation data set and the Microsoft GrabCut database demonstrate that the proposed method outperforms state-of-the-art methods.